Accounting for aerodynamic Interference effects for a quadplane in transition flight - Shahriar, Fahim (2019)
Quadplane is a unique unmanned air vehicle (UAV) which has horizontal rotors and fixed wings. This prominent formation allows the vehicle to take off or land vertically, hover and transit to horizontal flight. This thesis explores and demonstrates the aerodynamic interference appearing between the wings of a quadplane in its transition phase, for better perception of its performance and wing orientations. Numerical models are established using the lumped vortex model, to analyse the upwash and downwash effects from the wings for unsteady loads and moments. Influence of upwash encountered by the front-wing and downwash on the back-wing are recognized from the dissimilar lift outcomes. The study is done for two separate tandem wing layouts consisting of symmetric wings and cambered wings. Results show that, both wing arrangements are found to be analogous with different vehicle trim conditions. Quasi-steady evaluation of the quadplane models are compared to the unsteady solutions process to examine the importance of unsteady interactions. An analysis is performed to address the effects of a disturbance on the moving quadplane. Full flight simulations of the quadplane models are performed with the utilization of tuned controllers. The simulations are conducted for the specified cases of wing interactions and quasi-steady analysis to investigate the respective 3–DoF longitudinal dynamics of the quadplanes.